(untitled) (International Seven Journal of Multidisciplinary, 2025)
Objective: To analyze the relationship between the viral load of the canine distemper virus in the cerebrospinal fluid and the severity of neurological manifestations in dogs, evaluating the main diagnostic methods, the progression of the disease and possible therapeutic approaches. Canine distemper is a highly contagious viral disease that can cause severe neurological impairment, with demyelinating encephalitis being one of the main consequences of infection in the central nervous system (CNS). The breakdown of the blood-brain barrier, driven by matrix metalloproteinases and an intense inflammatory response, allows the virus to enter the cerebrospinal fluid, increasing the severity of symptoms. Studies show that dogs with a high concentration of virus in the cerebrospinal fluid exhibit more severe clinical conditions, such as myoclonus, ataxia, seizures and proprioceptive deficits, in addition to a higher mortality rate. The diagnosis of neurological distemper can be complex due to its similarity to other neurological diseases. CSF RT-PCR is one of the most sensitive and specific techniques to confirm infection. With regard to treatment, there is still no efficient specific antiviral, but studies indicate that ribavirin can decrease the replication of the virus and increase the survival of infected dogs. Understanding the connection between viral load and neurological manifestations is crucial to improve diagnostic, prognostic and treatment tactics, aiding in the clinical control of canine distemper.